2018
DOI: 10.1039/c8gc01958d
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-free direct α-alkylation of ketones by alcohols catalyzed by nickel supported on silica–alumina

Abstract: The α-alkylation of acetophenone with benzyl alcohol through borrowing hydrogen has been studied using nickel catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…To this date, no non‐noble metal based heterogeneous catalyst has been reported for this reaction. Our group has been investigating the efficiency of Ni/SiO 2 –Al 2 O 3 for the α‐alkylation of ketones with alcohols, including methanol , . Furthermore, this catalyst has been fully characterized (see ESI).…”
Section: Base Screening For the N‐alkylation Of Phenylacetamide 1a Wimentioning
confidence: 99%
See 1 more Smart Citation
“…To this date, no non‐noble metal based heterogeneous catalyst has been reported for this reaction. Our group has been investigating the efficiency of Ni/SiO 2 –Al 2 O 3 for the α‐alkylation of ketones with alcohols, including methanol , . Furthermore, this catalyst has been fully characterized (see ESI).…”
Section: Base Screening For the N‐alkylation Of Phenylacetamide 1a Wimentioning
confidence: 99%
“…Our group has been investigating the efficiency of Ni/SiO 2 -Al 2 O 3 for the αalkylation of ketones with alcohols, including methanol. [33,34] Furthermore, this catalyst has been fully characterized (see ESI). Herein, we report our new findings on the catalytic activity of Ni/SiO 2 -Al 2 O 3 for the solvent-free N-alkylation of amides with alcohols.…”
mentioning
confidence: 99%
“…These observations show that the leaching of the catalyst does not play a decisive role in the deactivation of the recycled catalyst. The recyclability of the Ni catalyst for the α‐methylation of ketones with methanol is in contrast with the excellent recyclability of the same catalyst for the alkylation of acetophenones with other alcohols . Further studies will be performed to fully understand how the catalyst deactivates in the presence of methanol under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the works previously cited mostly rely on noble and expensive metals, and there is to date no example of non‐noble metal heterogeneous catalysts. We have previously reported that Ni/SiO 2 ‐Al 2 O 3 is an efficient, inexpensive and recyclable supported catalyst for the α‐alkylation of ketones by benzylic and long chain aliphatic alcohols . Herein, we report the α‐methylation of ketones catalyzed by Ni/SiO 2 ‐Al 2 O 3 using methanol as an alkylating agent (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of these highly expensive ligands and their multistep synthesis often is a major concern. Recently, supported heterogeneous metal catalysts, for example, Pd, Ru, Cu, and Ni– have also been developed for ɑ‐alkylation of ketones with primary alcohols. Although these offer a green and sustainable approach for α‐alkylation of ketones, a large excess of base (up to 300 mol%) and the presence of hydrogen acceptor are necessary, and even sometimes accompany with the over‐reduction of the targeted products in some cases.…”
Section: Optimization Of Reaction Conditionsamentioning
confidence: 99%